2012
DOI: 10.1111/j.1476-4431.2012.00772.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of strong ion gap in healthy dogs

Abstract: The 2 equations used to calculate SIG yielded significantly different results and cannot be used interchangeably. The authors believe SIG(2) to be a more accurate reflection of acid-base status in healthy dogs, and recommend that this calculation be used for future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 30 publications
5
13
4
Order By: Relevance
“…The SIG determination provides an estimate for the difference between the unmeasured strong anion charge and unmeasured strong cation charge. Similar to SID, many different methods of calculation and consequently reference intervals have been reported in the literature . In the present study SIG was calculated using an equation based on canine values for A tot and K a , and the values we found in control dogs were higher than the SIG range of −5.0 to 5.4 mEq/L reported by Constable et al A possible explanation for this finding could be related to the analyzer used in the study.…”
Section: Discussionsupporting
confidence: 40%
“…The SIG determination provides an estimate for the difference between the unmeasured strong anion charge and unmeasured strong cation charge. Similar to SID, many different methods of calculation and consequently reference intervals have been reported in the literature . In the present study SIG was calculated using an equation based on canine values for A tot and K a , and the values we found in control dogs were higher than the SIG range of −5.0 to 5.4 mEq/L reported by Constable et al A possible explanation for this finding could be related to the analyzer used in the study.…”
Section: Discussionsupporting
confidence: 40%
“…In the normal patient the SIG should approach zero. The comparison values for SIG in the present study are similar to what has been reported previously for dogs and cats . The SIG identified more patients with unmeasured anions than the AG in this study.…”
Section: Discussionsupporting
confidence: 91%
“…The comparison values for SIG in the present study are similar to what has been reported previously for dogs and cats. 14,[32][33][34] The SIG identified more patients with unmeasured anions than the AG in this study. Human studies have reported similar findings although there is little difference in performance if the AG is corrected for hypoalbuminemia.…”
Section: Discussionmentioning
confidence: 62%
“…19 It has been previously shown that there are significant differences between SIG when it is calculated using different equations. 22 The data generated in the PE group were compared to the control dog data to arrive at an acid-base diagnosis ( Table 2). Using this model the following acid-base diagnoses could be reached based on whether SID, A tot , and SIG were increased/decreased according to Table 3; SID acidosis/alkalosis, A tot acidosis/alkalosis, and the presence of UA acidosis as evidenced by an increase in the SIG.…”
Section: Use Of a Validated Data Modelmentioning
confidence: 99%